EFEKTIVITAS RETENSI DAN PEMUSNAHAN BERKAS REKAM MEDIS DALAM MENGHADAPI ERA DIGITALISASI DATA DI PUSKESMAS BARENG MALANG : The Effectiveness of Retention and Destruction of Medical Record Files in Facing The Era of Data Digitization at Bareng Public Health Center Malang - Fita Rusdian Ikawati; Retno Dewi Prisusanti; Achmad Jaelani Rusdi (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
In the era of digitalization of medical record data, information technology is used to document patient health data quickly and accurately, so it is necessary to make decisions using electronic medical records. Digitalization of medical records is a process of transitioning medical record document media into digital documents using a scanner. Public Health Center together in September 2022, the retention process that occurred was still at the selection stage and in the medical record storage room, active and inactive files were still found that were still on one storage shelf, while destruction had already been carried out by shredding. This research aims to determine the effectiveness retention and destruction of medical record files in the era of data digitization. This type of research uses qualitative descriptive methods and data collection methods are carried out by observation and interviews. The subjects of this research were the head of the medical records unit and the medical records officer. The results of this research showed that the medical record file storage system already has an SOP, the retention of medical records has a policy stated in the SOP, and the destruction of medical record files has an SOP and was carried out for the first time in 2018.